2018
DOI: 10.1155/2018/1780683
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Type 2 Diabetes Mellitus on Long-Term Prognosis in Patients of Different Ages with Myocardial Infarction

Abstract: The objective of the study was to assess the impact of DM2 at baseline on long-term mortality after acute myocardial infarction (MI) among different age groups. The data were taken from: “Register of Acute Myocardial Infarction.” A total of 862 patients were followed for five years after acute myocardial infarction. The primary endpoint was death from any cause. The patients were categorized into 2 groups based on their ages: group 1—comprised patients older than working age (n = 358) and group 2—comprised emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
(24 reference statements)
1
13
0
1
Order By: Relevance
“…The VALIANT trial showed that both previously known diabetes and incident diabetes increased the risk of new cardiovascular events and death after an acute myocardial infarction [21]. Other authors have reported an even higher impact on behalf of T2DM on the prognoses of the elderly patients after a myocardial infarction than in younger patients [22]. Moreover, the increased mortality risk conferred by T2DM has also been described for stroke [23].…”
Section: Discussionmentioning
confidence: 98%
“…The VALIANT trial showed that both previously known diabetes and incident diabetes increased the risk of new cardiovascular events and death after an acute myocardial infarction [21]. Other authors have reported an even higher impact on behalf of T2DM on the prognoses of the elderly patients after a myocardial infarction than in younger patients [22]. Moreover, the increased mortality risk conferred by T2DM has also been described for stroke [23].…”
Section: Discussionmentioning
confidence: 98%
“…The VALIANT trial showed that both previously known diabetes and incident diabetes increased the risk of new cardiovascular events and death after an acute myocardial infarction [21]. Other authors have reported an even higher impact on behalf of T2DM on the prognoses of the elderly patients after a myocardial infarction than in younger patients [22]. Moreover, the increased mortality risk conferred by T2DM has also been described for stroke [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that type 2 DM increases 5-year mortality in elderly patients with AMI. While younger patients with AMI and type 2 DM are more likely to have complications in the early period after AMI compared to patients of the same age group but without type 2 DM [6]. The adverse effect of DM on in-hospital mortality rates after AMI was further confirmed by a recent cohort study including more than 5,000 STEMI patients following primary PCI [7].…”
Section: Introductionmentioning
confidence: 90%